What's in it for Me? : A Primeron Differences between Islamic and Conventional Finance in Malaysia - Krasicka, Olga (IMF Working Papers; Working Paper ;, 2012)
What attracts conventional investors to Islamic financial instruments? We answer this question by comparing Malaysian Islamic and conventional security prices and their response to macrofinancial factors. Our analysis suggests that Islamic and conventional bond and equity prices are driven by common factors. Likewise, especially in recent years, Islamic banks have responded to economic and financial shocks in the same way as conventional banks, suggesting that the gap between Islamic and conventional financial practices is shrinking.